Cheerful Memories/Troubled Years : a Story of a Refusenik's Family in Leningrad and its Struggle for Immigration to Israel - Taratuta; Taratuta, Ida (Boston, MA : Academic Studies Press, 2019)
This book captures the story of the Taratuta family and their struggle to flee the hardships of the USSR and repatriate to Israel in the late twentieth century. The narrative follows the lives of three family members, Aba, his wife Ida, and their son Misha, as they endure countless struggles throughout their journey to freedom. Tense moments ensue as the refuseniks print copies of forbidden Zionist literature and textbooks, publicly support those detained in prison and the Gulag, organize scientific and legal seminars in their apartment, receive Western visitors, and secretly partake in weekly Hebrew lessons. Well-recognized in the West as central players in the Soviet Jewish movement in Leningrad throughout the 1970s and 1980s, the Taratutas underwent constant surveillance by the KGB until they were finally able to repatriate to Israel. In spite of their hardships, the family attempted to live a life of normalcy and to cherish moments of happiness and togetherness.
Frontmatter -- Contents -- From the Editor -- From the Authors -- 1. Grandmother Ida -- 2. Grandfather Aba -- 3. Father Michael (Misha) -- 4. Hebrew -- 5. Samizdat -- 6. Demonstrations, 1974 -- 7. The Phone -- 8. Seminars -- 9. Unsanctioned exhibition -- 10. Pesach 1977 -- 11. Warning -- 12. Visits to places of detention -- 13. The Search -- 14. An Investigation at the Public Prosecutor's office -- 15. The Jewish Library -- 16. Interrogation at the KGB, 1982 -- 17. Burglary -- 18. Our Contacts with the West -- 19. Three Demonstrations, 1987 -- 20. Not by Zionism alone -- 21. Israel -- Afterword -- Appendix. Aba's refusenik diary
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 21. Dez 2019).
WorldCat record variable field(s) change: 072
Keywords: Taratuta, Aba -- Family; Refuseniks; Jews -- Persecutions -- Soviet Union; Jews -- Soviet Union -- Migrations; Soviet Union -- Emigration and immigration -- Government policy; Soviet Union -- Ethnic relations; Israel -- Emigration and immigration; BIOGRAPHY & AUTOBIOGRAPHY -- Social Activists; Emigration and immigration; Emigration and immigration -- Government policy; Ethnic relations; Families; Jews -- Migrations; Jews -- Persecutions; Refuseniks; Israel; Soviet Union; BIOGRAPHY & AUTOBIOGRAPHY / Social Activists; Electronic books